Prediction of soil loss in a reservoir watershed using an erosion model and modern technological tools: a case study of Marathon Lake, Attica in Greece. - Xanthakis, M; Pavlopoulos, K.; Kapsimalis, V.; G. Apostolopoulos; Xanthopoulos, G.; Stefanidis, P.; Evelpidou, N. (Environmental Science Proceedings, 2020)
Marathon Lake is an artificial reservoir with great environmental, ecological, social, and economic significance because it was the main source of water for Athens, the capital of Greece, for many years. The present study details the first attempt to map sedimentation in Marathon Lake in detail, using bathymetric mapping and soil erosion field surveying of the torrent watershed areas. First, the results of a bathymetric survey carried out in 2011 were compared with topographic maps that pre-date the construction of the dam. Based on this comparison, an estimated 8.34 hm3 of sediment have been deposited in the 80 years since the dam’s construction. In the current survey, the Revised Universal Soil Loss Equation (RUSLE) was used to estimate soil loss in the watershed area of the streams that end in Marathon Lake. The estimated value from the RUSLE was substantially lower (3.02 hm3) than that calculated in the bathymetric survey.